Euphonic: inelastic neutron scattering simulations from force constants and visualization tools for phonon properties. Issue 6 (29th November 2022) - Fair, Rebecca; Jackson, Adam; Voneshen, David; Jochym, Dominik; Le, Duc; Refson, Keith; Perring, Toby
Abstract : An overview of the Euphonic Python package for efficient simulation of inelastic neutron scattering by phonons from force constants is presented. Abstract : Interpretation of vibrational inelastic neutron scattering spectra of complex systems is frequently reliant on accompanying simulations from theoretical models. Ab initio codes can routinely generate force constants, but additional steps are required for direct comparison with experimental spectra. On modern spectrometers this is a computationally expensive task due to the large data volumes collected. In addition, workflows are frequently cumbersome as the simulation software and experimental data analysis software often do not easily interface to each other. Here a new package, Euphonic, is presented. Euphonic is a robust, easy to use and computationally efficient tool designed to be integrated into experimental software and able to interface directly with the force constant matrix output of ab initio codes.